In vivo anxiolytic and in vitro anti-inflammatory activities of water-soluble extract (WSE) of Nigella sativa (L.) seeds. Issue 16 (12th August 2021) - Babar, Z. M.; Jaswir, I.; Tareq, A. M.; Ali Reza, A. S. M; Azizi, W. M.; Hafidz, M.; Ahfter, F.; Hasan, M.; Farhad, S.; Uddin, M. M. Rokib; Ichwan, S.JA.; Ahmed, Q. U.; et al.
Abstract: The WSE is a highly polar, gummy and mucilaginous bioactive content of the Nigella sativa (L.) seeds. This study reports the anxiolytic and anti-inflammatory effects of WSE investigated using Elevated Plus Maze (EPM) and Hole-Board Test (HBT) in adult mice and human RBCs haemolysis inhibition and protein denaturation respectively. The oral WSE treatment (100 & 200 mg/kg b.w/day) for 72 hours has exhibited slightly better anxiolytic effect ( p  < 0.05) through the time span (92.33 & 93.33 s) spent in the opened arms of EPM vs . diazepam (1 mg/kg b.w i.p/day; 69.33 s). In HBT, only WSE (200 mg/kg b.w/day) has shown a promising number of mean head pokes (13.27 times/min) vs . diazepam (12.87 times/min). The WSE (62.5-500 µg/mL) exposure has exhibited 40.14‐72.18% protection against lysis of RBCs vs . aspirin (57.04-71.48%) whilst 62.67-67.66% inhibition of protein denaturation vs . diclofenac sodium (43.11-80.64%). The current findings suggested WSE has promising anxiolytic and anti-inflammatory activities. Graphical Abstract: